Competition analysis of automobiles and light commercial segment between 1990 and 2014 - Daniel Santana Medeiros (Socioeconomic Analytics)
This paper reviews the concept of market structure in oligopoly and concentration indicators CR(4) and HH, and verifies the changes in the concentration and competition of the automotive and light commercial market between 1990 and 2014. In 1990, the CR(4) that represents the participation of the four largest firms that was 98.8% becomes 95.1% at the end of 1996, and the HH index that varies between 1/n and 1, being 1 monopoly situation dominated by a company and without competition and 1/n varying the competition as more companies enter the sector, it goes from 0.2951 in 90 to 0.2756 in 96, pointing out the sector as concentrated and competitive, characteristic of oligopoly. These indicators continue to change in the following years and in 2014 the CR(4) is 64.9% and the HH index measures 0.1700, showing that the sector is less concentrated and more competitive. The review addresses the market characteristics in the oligopoly whether or not it´s concentrated and competitive in Brazil from 1990 to 2014 divided into two periods, the first from 90 to 96 and the second from 97 to 2014. The characteristic of the car and light commercial market in the first period indicates for a sector with the characteristic of a very concentrated and competitive oligopoly. For the second period analyzed, a much less concentrated and more competitive sector.